2019
DOI: 10.3389/fchem.2019.00536
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Proton Transfer on Mutations

Abstract: Hydrogen bonds play a critical role in nucleobase studies as they encode genes, map protein structures, provide stability to the base pairs, and are involved in spontaneous and induced mutations. Proton transfer mechanism is a critical phenomenon that is related to the acid–base characteristics of the nucleobases in Watson–Crick base pairs. The energetic and dynamical behavior of the proton can be depicted from these characteristics and their adjustment to the water molecules or the surrounding ions. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 189 publications
(223 reference statements)
1
36
0
Order By: Relevance
“…The ability to display the contribution of intra- and inter-molecular variation of the charge density following inner shell ionization provides valuable information on the stability of hydrogen-bonded biomolecules, like for example DNA base pairs in interaction with a damaging radiation. It is indeed known that charge transfer via hydrogen bond, like for example the transport of the protons, can lead to induced and spontaneous mutations 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The ability to display the contribution of intra- and inter-molecular variation of the charge density following inner shell ionization provides valuable information on the stability of hydrogen-bonded biomolecules, like for example DNA base pairs in interaction with a damaging radiation. It is indeed known that charge transfer via hydrogen bond, like for example the transport of the protons, can lead to induced and spontaneous mutations 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…[45] Proton transfer is also observed, at low temperature, in cationic adenine-thymine stacks,i nitiating important competition to catch the protonb y different electron lone pairs in the surrounding environment. [24] The role of water molecules wasp ut forwarda st he triggering factor leading to proton transfer,e ven if the precise molecular mechanism and the role of hydration were not completely analyzed.R ecently,t he photo-oxidation and quenching of guanine radical cations in aG -quadruplex environment has also been studied by QM/MM dynamics at multiconfiguration level. More specifically,apreference for the deprotonation of the imino protono faguanine in the loop has been observed, which is coherent with the fact that the deprotonation appears to be facilitated for moietiest hat are not engaged in hydrogen bonds with other nucleobases.…”
Section: Resultsmentioning
confidence: 99%
“…These include protone xchanges in the hydrogen-bonded nucleobases, leading to the formationo f' rare tautomers'. [24] Notably,Z engtao et al observed that proton trans-fer at low temperatures is assisted by water through displacement polarization and oriented polarization mechanisms. [25] Particular attention has been devoted in the past to chemical reactions triggered under the ionization of DNA nucleobases.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Löwdin works [26][27][28][29] , which suggested that the genetic code stored in the DNA depends upon the stability of the hydrogen-bonded base pairs and the transport of the protons along these hydrogen bonds, several important works were devoted to understanding the endogenous spontaneous DNA mutations which origin is not yet elucidated. These include proton exchanges in the hydrogenbonded nucleobases leading to the formation of "rare tautomers" 30 . Notably, Zengtao et al observed that proton transfer at low temperatures is assisted by water through displacement polarization and oriented polarization mechanisms.…”
mentioning
confidence: 99%
“…Proton transfer is also observed, at low temperature, in cationic adenine-thymine stacks, initiating important competition to catch the proton by different electron lone pairs in the surrounding environment 30 . Although, the role of water molecules was put forward as the triggering-factor leading to proton transfer, the precise molecular mechanism and the role of hydration were not completely analyzed.…”
mentioning
confidence: 99%